MINIATURE TWO-FINGERED ROBOT HAND DRIVEN BY MUSCLE WIRES ACTUATORS - Al-Ammri, A. Salam; Kadim, Bahaa I.; Al-Azzawi, Yarub O. (Al-Khwarizmi Engineering Journal, 2019)
In this research, a modified artificial hand with direct control has been designed using electrical artificial muscle wires that receive direct sensory impulses through human hand instead of using the mechanical action to open and close this artificial hand. Each finger is designed as a chain and its movements achieved through the conventional arrangement control of the electrical muscles wires. The results indicate that it is possible to design an artificial hand using electrical muscle wire for control it with high accuracy.